The Effect Of Lean Six Sigma Supply Chain And Sustainability Disclosure On Poultry Farming Issuers - Jabani, Muzayyanah; Yasir, Jibria Ratna; Zulkarnain, Agung (International Journal of Economics (IJEC), 2025)
This study aims to analyze the effect of Lean Six Sigma Supply Chain disclosure and sustainability disclosure on company performance among poultry farm issuers listed on the Indonesia Stock Exchange. Lean Six Sigma practices within the supply chain are regarded as capable of enhancing operational efficiency through waste reduction, quality improvement, and the optimization of material and information flows. Concurrently, sustainability disclosure is increasingly demanded by stakeholders as an indicator of a company's commitment to economic, social, and environmental considerations. This research employs a quantitative methodology, utilizing frame analysis and content analysis of annual reports and sustainability reports to assess the extent of disclosure for both variables. Furthermore, the data were analyzed using SEM PLS (Partial Least Squares), as this method is suitable for complex models involving numerous variable indicators and constructs, with the objective of evaluating the predictive model. The findings indicate that, overall, the disclosure of Lean Six Sigma Supply Chain practices has increased among PT CPIN, PT Malindo, and PT Sierad. PT Malindo demonstrated a consistent increase in sustainability report disclosure, whereas PT CPIN exhibited slight fluctuations in its sustainability disclosures. PT Sierad showed an increase, although from 2017 to 2019, it maintained the same disclosure index value. These results highlight the significance of integrating operational efficiency practices with sustainability transparency as a strategy to improve the competitiveness and long-term value of poultry farming issuers.